The role of music familiarity, mood-based music selection, and music listening frequency on emotional wellbeing among Malaysian youth - Mohamed Razali, Camellia Siti Maya; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
This study explores the relationship between music familiarity, mood-based music selection, music listening frequency, and emotional wellbeing among Malaysian youth aged 18-30, recruited from public and private universities across Malaysia. A quantitative approach was employed with a sample of 395 participants, utilizing Pearson correlation and multiple regression analyses to investigate the impact of these variables on emotional wellbeing. The findings revealed that mood-based music selection was the strongest predictor of emotional wellbeing, followed by music familiarity and music listening frequency. These results suggest that youth who intentionally select music to match or alter their mood, engage with familiar music, and frequently listen to music experience higher emotional wellbeing. The study underscores the importance of music in emotional regulation and highlights the potential of music-based interventions in mental health programs. Educational institutions and policymakers are encouraged to integrate music-based strategies to enhance emotional wellbeing among youth. Future research could explore these relationships further across diverse cultural and age groups.